Wideband DS-CDMA for next-generation mobile communications systems. - Adachi, F.
Wideband wireless access based on direct sequence code division multiple access aimed at third-generation mobile communications systems is reviewed. W-CDMA is designed to flexibly offer wideband services which cannot be provided by present cellular systems, with various data rates as high as 2 Mb/s. The important concept of W-CDMA is the introduction of intercell asynchronous operation and the pilot channel associated with individual data channels. Intercell asynchronous operation facilitates continuous system deployment from outdoors to indoors. Other technical features of W-CDMA include fast cell search under intercell asynchronous operation, fast transmit power control, coherent spreading code tracking, a coherent RAKE receiver, orthogonal multispreading factor forward link, and variable-rate transmission with blind rate detection. The introduction of the data-channel-associated pilot channel allows W-CDMA to support interference cancellation and adaptive antenna array techniques that can significantly increase the link capacity and coverage. This article presents the radio link performance evaluated by computer simulation. Field experiment radio link performance results are also presented
Keywords: 2 Mbit/s.; W-CDMA.; Adaptive antenna array; Blind rate detection; Cellular systems; Coherent RAKE receiver; Coherent spreading code tracking; Computer simulation; Data channels; Data rates; Direct sequence code division multiple access; Fast cell search; Fast transmit power control; Field experiment; Intercell asynchronous operation; Interference cancellation; Link capacity; Link coverage; Next-generation mobile communications systems; Orthogonal multispreading factor forward link; Pilot channel; Radio link performance; Variable-rate transmission; Wideband DS-CDMA.; Wideband services; Wideband wireless access